2023
DOI: 10.1017/s0954579423001013
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic indicators predict developmental changes in cognitive control resting-state networks

Giorgia Picci,
Nathan M. Petro,
Jake J. Son
et al.

Abstract: Over the past decade, transdiagnostic indicators in relation to neurobiological processes have provided extensive insight into youth’s risk for psychopathology. During development, exposure to childhood trauma and dysregulation (i.e., so-called AAA symptomology: anxiety, aggression, and attention problems) puts individuals at a disproportionate risk for developing psychopathology and altered network-level neural functioning. Evidence for the latter has emerged from resting-state fMRI studies linking mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Given that previous research has not yet shown that DHEA levels and pituitary volume amplify risk for specific diagnostic categories, the current study employed a more transdiagnostic approach. We built off of previous work highlighting that dysregulation is a potent predictor of long-term psychopathology diagnoses and comorbidities (Althoff and Ametti, 2021), as well as changes in key neural networks (Picci et al, 2023b). Dysregulation is often defined as difficulties in regulating affect, behavior, and cognition (ABCs), with symptoms peaking during early adolescence (Deutz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Given that previous research has not yet shown that DHEA levels and pituitary volume amplify risk for specific diagnostic categories, the current study employed a more transdiagnostic approach. We built off of previous work highlighting that dysregulation is a potent predictor of long-term psychopathology diagnoses and comorbidities (Althoff and Ametti, 2021), as well as changes in key neural networks (Picci et al, 2023b). Dysregulation is often defined as difficulties in regulating affect, behavior, and cognition (ABCs), with symptoms peaking during early adolescence (Deutz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%